2017
DOI: 10.1016/j.cobme.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Progress and remaining challenges in the application of high frequency oscillations as biomarkers of epileptic brain

Abstract: High-frequency oscillations (HFOs: 100 – 600 Hz) have been widely proposed as biomarkers of epileptic brain tissue. In addition, HFOs over a broader range of frequencies spanning 30 – 2000 Hz are potential biomarkers of both physiological and pathological brain processes. The majority of the results from humans with focal epilepsy have focused on HFOs recorded directly from the brain with intracranial EEG (iEEG) in the high gamma (65 – 100 Hz), ripple (100 – 250 Hz), and fast ripple (250 – 600 Hz) frequency ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Most of the employed detectors suffer from high specificity and are not able to distinguish physiological HFOs, high-frequency artifacts, false oscillations due to the filtering of sharp transient from pathological HFOs that is a category consisting itself in different possible groups (e.g., ripples, fast ripples, and fast ripples during ripples). In general, thanks to the employment of machine learning, it is not necessary to assume that HFOs are rare events and to define manually a threshold, therefore the typical high number of false positive of traditional automatic detectors decreases [53]. Moreover, recently, it has been highlighted that it is necessary to further refine HFO identification, differentiating HFOs with respect to the baseline from HFOs occurring during spikes, and defining different thresholds for SOZ identification, varying according to brain regions [54].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the employed detectors suffer from high specificity and are not able to distinguish physiological HFOs, high-frequency artifacts, false oscillations due to the filtering of sharp transient from pathological HFOs that is a category consisting itself in different possible groups (e.g., ripples, fast ripples, and fast ripples during ripples). In general, thanks to the employment of machine learning, it is not necessary to assume that HFOs are rare events and to define manually a threshold, therefore the typical high number of false positive of traditional automatic detectors decreases [53]. Moreover, recently, it has been highlighted that it is necessary to further refine HFO identification, differentiating HFOs with respect to the baseline from HFOs occurring during spikes, and defining different thresholds for SOZ identification, varying according to brain regions [54].…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard is visual identification, 7,14,15 but automated detectors are increasingly being implemented to save time and improve reliability and reproducibility 16,17 . Automatic detection algorithms generally follow a standard procedure: They identify a period of increased high‐frequency energy (measured with root‐mean‐square (RMS) amplitude, 15,18,19 amplitude of rectified filtered data, 20,21 line length, 22,23 Hilbert envelope, 3,24 or as a peak in the time‐frequency decomposition 25 ), then verify that the event exceeds a minimum duration or a minimum number of oscillations. Many algorithms include additional steps to merge consecutive events if they occur in close temporal proximity 3,18,26 and reject false positives 3,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…First, visual and automated detection rely on the empirical definition of an HFO derived from visual observation 12 . There is currently no physiological definition that can guide the selection of detection parameters such as amplitude, duration, and number of cycles, as studies have shown significant overlap between pathological and physiological HFOs 23,25,30‐32 . However, the optimization of such parameters is critical to the accuracy of the detector 15,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for detection is visual identification, 8,[16][17][18] but automated detectors are increasingly being implemented to save time and improve reliability and reproducibility. 19,20 Automatic detection algorithms generally consist of the same basic steps: they identify a period of increased high frequency energy (measured with root-mean-square (RMS) amplitude, 17,21,22 amplitude of rectified filtered data, 23,24 line length, 25,26 Hilbert envelope, 3,4,27 or as a peak in the time-frequency decomposition 28 ), then verify that the event exceeds a minimum duration or a minimum number of oscillations. Many detection algorithms include additional steps to merge consecutive events and reject false positives.…”
Section: Introductionmentioning
confidence: 99%
“…14 There is currently no clear physiological definition that can be used to guide the selection of detection parameters such as amplitude, duration, and number of cycles, as studies have shown significant overlap between pathological and physiological HFOs. 26,[28][29][30][31] However, the optimization of such parameters is critical to the accuracy of the detector. 17,23,24 This is directly related to the second challenge: existing detection methods require complex optimization procedures.…”
Section: Introductionmentioning
confidence: 99%